The Role of Pancreatic Enzyme Insufficiency in the Etiology of Functional Dyspepsia Resistant to Standard Treatment - Kemik, Fatih (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Kemik F. The role of pancreatic enzyme insufficiency in the etiology of functional dyspepsia resistant to standard treatment. Turk J Gastroenterol. Published online October 31, 2025. doi:10.5152/tjg.2025.255322